Prawo do posiadania i noszenia broni w II Poprawce do Konstytucji Stanów Zjednoczonych Ameryki - ujęcie oryginalistyczne - Bartosik, Łukasz (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2017)
The purpose of this paper is to present an originalist interpretation of the II Amendment to the U.S. Constitution, which guarantees the right to keep and bear arms for the American citizens. The article, in a holistic manner, depicts the fundamental problems and the main interpretative strands of the law, as well as provides its scrupulous historical and linguistic analysis. The problems which are being evaluated, consist of the general legal character of the regulation and the meaning of the terms articulated therein, such as “militia”, “state”, “people”, “keep”, “bear” and “arms”. The interpretative conclusions of this paper significantly overlap with the originalist argumentation presented to the U.S. Supreme Court in a remarkable case Heller v. District of Columbia from 2008 in which the Court ruled establishing the judiciary line of authority stressing the individualist theory of the right to keep and bear arms. This paper, although based on the American legal experiences, could also be an important voice in the debate on gun rights in Poland.